Learning Processes in Absorptive Capacity in Project-Based Organizations - Rodrigo Teixeira; Isabel Cristina Scafuto; Roberto Lima Ruas; Fernando Ribeiro Serra; Carlos Ricardo Rossetto (SAGE Open)
Projects are means used by companies to achieve their strategies. Often, the success of a project depends on the ability of its members to access, absorb, and apply the multiple knowledge opportunities that exist within and through the projects. Considering the importance of knowledge for project management in project-based organizations, as well as the role that learning processes of absorptive capacity play in the organization, this study aims to characterize the main learning processes within absorptive capacity in project-based organizations, focusing on how these processes manifest and impact project management practices. A qualitative approach was employed through multiple case studies of two project-based organizations. Data collection involved semi-structured interviews and document analysis, allowing a comprehensive view of absorptive capacity in real project settings. Findings reveal that project-based organizations utilize four primary learning processes in absorptive capacity: exploratory, assimilative, transformative, and exploitative learning. Notably, there is a tendency toward exploratory learning, resulting in an imbalance across learning processes that affects absorptive capacity’s effectiveness. This study contributes to the absorptive capacity literature by detailing practices associated with each learning process in project-based organizations, thus offering insights into their role in managing knowledge within dynamic project environments.